USING REDW STRATEGY TO IMPROVE NURSING STUDENTS’ READING COMPREHENSION IN AKPER PRIMA JAMBI - Silvia, Resi (SCIENTIA JOURNAL, 2017)
This paper highlights the findings of a study which was undertaken at AKPER Prima Jambi. Theaim of the study was to describe how the Read-Examine-Decide-Write (REDW) strategy canimprove reading comprehension. The data were taken from observation, field notes, questionnaire,and achievement test. The result reveals that the REDW not only improves students' readingcomprehension but also increases their motivation in learning.